Perceptual Learning Styles and Teacher Professional Development Needs in Ethiopian Secondary Schools: Implications for Educational Policy and Planning - Sisay Fekadie Molla; Tarik Derso Belay (Educational Researcher Journal, 2026)
This study examined the predictive relationship between perceptual learning styles and teacher professional development needs among 423 Grade 11 students and 12 English language teachers in Gondar, Ethiopia, with a focus on its implications for educational policy and planning. Using a quantitative correlational design, data were collected through Reid's (1987) Perceptual Learning Style Preference Questionnaire and a Teacher Professional Development Needs Assessment Scale. Multiple regression analysis revealed that learning styles collectively accounted for 96.3% of the variance in teacher professional development needs (R² = .963, F = 10960.666, p < .001). Kinesthetic learning emerged as the strongest predictor of professional development needs (β = .854, R² = .730), followed by read/write (β = .718, R² = .515), visual (β = .643, R² = .413), and auditory learning (β = .577, R² = .334). These findings indicate that teachers' ability to address kinesthetic learning preferences is the most significant predictor of professional development needs in the Ethiopian context. The findings have significant implications for educational policy and planning, suggesting that educational leaders and policymakers should prioritize professional development programs that equip teachers with differentiated instruction strategies, particularly kinesthetic approaches. The study contributes to educational planning by providing empirical evidence for evidence-based policymaking and strategic professional development planning in Ethiopian secondary education.